The Importance of a PM&R Consultation for Becker Muscular Dystrophy Patients Admitted with Cardiomyopathy - Neyha Cherin; Shivani Patel; Michelle Jukic (Case Reports in Cardiology)
Becker muscular dystrophy (BMD) is a rare genetic disorder that is associated with significant cardiac compromise, including heart failure and cardiomyopathy. Given the significant cardiac impact of the disease, patients are commonly hospitalized under the care of cardiologists. While it is imperative to address the acute cardiac challenges these patients face, it is crucial to not disregard the musculoskeletal derangement that occurs from this underlying disease and how acute hospitalization can exacerbate these issues. While literature focuses heavily on providing management protocols to address these acute cardiac complications, it is also important for providers to feel supported in addressing the functional implications that hospitalized BMD patients may face. An early PM&R consultation in the inpatient setting can be useful in identifying and addressing the functional impairments and subsequent comorbidities of BMD patients. PM&R teams can provide oversight from multiple avenues including the psychosocial, neurocognitive, durable medical equipment, and pain management perspectives and assist with transition of care to the postacute rehabilitation setting. The ultimate goal of the PM&R provider is to work alongside the primary service and patient in order to assist with retaining independence, improving patient satisfaction, and most importantly improving quality of life both inside and outside of the hospital setting.